Mechanical Properties of Concrete Incorporating Rice Husk Ash and Wheat Straw Ash as Ternary Cementitious Material - Bheel, N. (Hindawi Limited, 2021)
Over the last decade, there has been a surge in research into possible cement substitute materials in concrete that are environmentally friendly, cost-effective, and socially beneficial. The alternatives include industrial and agricultural wastes, and their potential advantages can be achieved through recycling, repurposing, and renewing processes. With the use of these wastes as additional and replacement materials, significant energy savings and a reduction in cement use can be achieved, which helps to reduce carbon dioxide (CO2) emissions in the environment. Therefore, the use of rice husk ash (RHA) and wheat straw ash (WSA) as ternary cementitious material (TCM) in concrete can help reduce the impact on the environment and minimize the use of Portland cement (PC) in the concrete mixture. This research work is performed on the concrete blended with 0, 5, 10, 15, and 20 of RHA and WSA as TCM in the mixture. However, the purpose of this experimental work is to investigate the influence of RHA and WSA as TCM on the fresh (slump), physical (water absorption and density), and hardened properties (compressive strength, splitting tensile strength, and flexural strength) and drying shrinkage of concrete. In this regard, a total of 240 concrete samples (cylinders, cubes, and beams) were prepared with 1: 2: 4 mix proportions at 0.50 water-cement ratio and cured at 7 and 28 days, respectively. Moreover, the workability of green concrete is getting reduced as the quantity of TCM increases in the mixture. Besides, the compressive strength, splitting tensile strength, and flexural strength are enhanced by 12.65, 9.40, and 9.46 at 10 of TCM (5 RHA and 5 WSA) on 28 days consistently. Furthermore, the density and water absorption of concrete are reduced with the increase in the dosages of TCM on 28 days, respectively. In addition, the drying shrinkage is reduced with the increase in the quantity of TCM in concrete. Â© 2021 Naraindas Bheel et al.